1999
DOI: 10.1016/s0144-8617(98)00091-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic properties of carbohydrate-coated dendrimers

Abstract: The hydrodynamic properties of poly(propylene imine) dendrimers, modified with outer-surface b-thiolactosyl residues (''lactodendrimers'') of generation number 1-5, have been investigated by velocity sedimentation, translational diffusion, and viscosity measurements in 0.165% NaCl aqueous solution. It has been demonstrated that apparent molecular weights (from the Svedberg equation) M sD of synthetic lactodendrimers, determined by sedimentation and diffusion experiments, are consistent with complete functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 65 publications
4
13
0
Order By: Relevance
“…5 shows a sketch of the equilibrated simulation cell. Although no salts were included in the system, the values of the corresponding radius of gyration R gWATER obtained from these virtual experiments for the ®rst two generations are in very good agreement with the values obtained experimentally by Pavlov et al (1999) (see Table 2). This seems to con®rm the validity of the force ®eld selection and the reliability of the applied simulation conditions.…”
Section: The Lactodendrimerssupporting
confidence: 81%
See 2 more Smart Citations
“…5 shows a sketch of the equilibrated simulation cell. Although no salts were included in the system, the values of the corresponding radius of gyration R gWATER obtained from these virtual experiments for the ®rst two generations are in very good agreement with the values obtained experimentally by Pavlov et al (1999) (see Table 2). This seems to con®rm the validity of the force ®eld selection and the reliability of the applied simulation conditions.…”
Section: The Lactodendrimerssupporting
confidence: 81%
“…Since, however, their full application potentials (particularly in materials science and engineering) will not be realized before the understanding of their physical properties is considerably more advanced, in this work we report the ®rst results obtained from an investigation of the structural details of the ®rst two generations of LDs. In order to verify the validity of the data obtained on isolated structures, we report also the comparison of the information gained on the same structures in an aqueous environment with the available experimental data (Pavlov et al, 1999). Finally, we show and discuss the results obtained from an investigation of the interaction between LDs and four molecules of pharmaceutical interest.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the latter case, the scaling exponents are very sensitive to thermodynamic quality of the solvent [24]. Compared to other dendritic structures, such as PAMAM in methanol [1,25], carbohydrate coated PAMAM [26] and DAB modified by lactose-end groups [27] in aqueous buffers, similar exponents from 0.25 to 0.37 were obtained. Indeed, diffusion scaling indexes for dendrimers and dendrimer-like structures are in the vicinity of 1/3.…”
Section: Resultsmentioning
confidence: 89%
“…In several works the hydrodynamic properties of dendrimer molecules were measured by different techniques [9,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. It is reported that the intrinsic viscosity of dendrimer molecules is small and has a very low dependency on the molecular weight or that this dependency has a small maximum depending on the number of generations.…”
Section: Molecular Characteristics Of Poly(propylene Imine) Dendrimermentioning
confidence: 99%